Authigenic beryllium concentrations and ratios (10Be/9Be) of sediment core PS97/085-3 - Loftfield, Julia; Nowaczyk, Norbert R; Lembke-Jene, Lester; Frederichs, Thomas; Lachner, Johannes; Lamy, Frank; Rugel, Georg; Stübner, Konstanze; Adolphi, Florian
Core PS97/085-3 of the Drake Passage was taken via piston corer during Polarstern cruise ANT-XXXI/3. We obtained high resolution records of authigenic 10Be/9Be ratios in order to study the different impacts on 10Be deposition in marine sediments compared to ice cores. As changes in the atmospheric production of cosmogenic 10Be leave a global fingerprint in 10Be deposition fluxes this represents a powerful tool for the synchronization of climate archives. During the Laschamps geomagnetic field low (~ 41 ka BP) the global production rate of 10Be is expected to double. We therefore chose the depth interval covering this period (3.80 m – 7.60 m). For Be measurements 1.5 – 2.0 g of freeze dried samples of the core were leached (Gutjahr et al., 2007), purified (Loftfield et al., 2024), and measured via ICP-OES (9Be) and AMS (10Be; Lachner et al., 2023 and Rugel et al., 2016).